Stand-Alone Hybrid PV System by Using The Bypass Converter Topology to Optimize the Reliable of Device - Prasojo, Fadillah; Mardiayah, Nur Alif; Hidayat, Khusnul (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
One of the applications of DC-DC converters in photovoltaic-battery hybrid systems is a two-way converter used for battery charging. The power supplied to the two-way converter experiences twice the power lost during the battery charging process. Therefore, it is necessary to arrange a phovoltaic-battery hybrid system topology so that only one stage of power conversion occurs when charging the battery so that the power loss is smaller. The proposed topology of this system uses three DC-DC converters connected to a battery and a DC bus. The one-way converter used in this system allows cross-connection between other DC-DC converters. Two one-way converters connect the phovoltaics to the DC bus and the photovoltaics to the battery, and the other one-way converter connects the battery to the DC bus. The purpose of using a one-way converter for charging the battery is called a bypass converter so that charging the battery does not go through two power conversions which cause twice the lost power. To make the proposed system more reliable, an inverter is added to the self-contained photovoltaic-battery hybrid system. Therefore, a control system is needed to maintain the DC bus voltage as input to the inverter using a double-loop control system. The two-loop Proportional-Integral control system is used for the DC electricity section while the Proportional-Resonant control system is used as an inverter control to maintain the balance of AC power. The results of system testing using Simulink/Matlab simulations show that the proposed topology uses a one-way converter capable of carrying out the battery charging process and can control the flow of power while maintaining DC and AC voltages.